Eco-friendly and Convenient Synthesis of Biologically Active Polysubstituted Dihydro-2-Oxypyrroles Using Manganese (II) Nitrate Tetrahydrate at Ambient Temperatures - Mohamadpour, Farzaneh (UI Scholars Hub, 2019)
A convenient, expedient and efficient method for the synthesis of polysubstituted dihydro-2-oxypyrroles is described via the one-pot four-condensation of dialkyl acetylenedicarboxylate, formaldehyde, and amines (aromatic and aliphatic) at ambient temperature in the presence of Manganese (II) Nitrate Tetrahydrate (Mn(NO3)2.4H2O) as a cost effective and inexpensive catalyst. The present methodology provides a simple and eco-safe procedure for the synthesis of polysubstituted dihydro-2-oxypyrroles with some additional advantages, such as good to high yields, short reaction times, avoidance of hazardous or toxic catalysts, simplicity of operating and work-up procedures with no necessity for chromatographic purification steps.